Adsorption mechanism and collapse propensities of the full-length, monomeric A beta(1-42) on the surface of a single-walled carbon nanotube: a molecular dynamics simulation study - Jana, Asis K.; Sengupta, Neelanjana (Biophysical Journal, 2012)
Though nanomaterials such as carbon nanotubes have gained recent attention in biology and medicine, there are few studies at the single-molecule level that explore their interactions with disease-causing proteins. Using atomistic molecular-dynamics simulations, we have investigated the interactions of the monomeric A beta(1-42) peptide with a single-walled carbon nanotube of small diameter. Starting with peptide-nanotube complexes that delineate the interactions of different segments of the peptide, we find rapid convergence in the peptide's adsorption behavior on the nanotube surface, manifested in its arrested movement, the convergence of peptide-nanotube contact areas and approach distances, and in increased peptide wrapping around the nanotube. In systems where the N-terminal domain is initially distal from nanotube, the adsorption phenomena are initiated by interactions arising from the central hydrophobic core, and precipitated by those arising from the N-terminal residues. Our simulations and free energy calculations together demonstrate that the presence of the nanotube increases the energetic favorability of the open state. We note that the observation of peptide localization could be leveraged for site-specific drug delivery, while the decreased propensity of collapse appears promising for altering kinetics of the peptide's self-assembly.

Adsorption of the full length amyloid beta peptide on the carbon nanotube surface and the thermodynamic implications for fibrillogenesis - Sengupta, Neelanjana; Jana, Asis K. (Biophysical Journal, 2012)

Effect of the A30P mutation on the structural dynamics of micelle-bound alpha synuclein released in water: a molecular dynamics study - Chatterjee, Prathit; Sengupta, Neelanjana (European Biophysics Journal With Biophysics Letters, 2012)
Atomistic molecular dynamics simulation has been used to probe the effect of the A30P mutation on the structural dynamics of micelle-bound, helical alpha Synuclein when released in an aqueous environment. On the timescales simulated, the effect of the mutation on the secondary structure is restricted to local changes close to the mutation site in the N-terminal helical domain. The changes are transient, and all residues except Lys23 recover their initial structure. The local behavior due to the mutation gives rise to a global difference in the A30P mutant in the form of a permanent kink in the N-terminal helical domain.
Keywords: A30P mutation; Alpha synuclein; Kink formation; molecular dynamics simulation; Structural persistence

Basic structural motif and major biophysical properties of Amyloid-beta are encoded in the fragment 18-35 - Chandrakesan, Muralidharan; Sarkar, Bidyut; Mithu, Venus Singh; Rajiv M. Abhyankar; Bhowmik, Debanjan; Nag, Suman; Sahoo, Bankanidhi; Shah, Riddhi; Gurav, Sushma; Banerjee, Raja; Dandekar, Sucheta; Jose, Jaya C.; et al. (Chemical Physics, 2013)
Aggregation and misfolding of the amyloid beta (A beta) peptide is thought to initiate Alzheimer's disease (AD). Here we study the role played by its central segment (A beta(18-35)) in determining these properties. A beta(18-35) has a solubility of 18 mu M. The soluble fraction consists mainly of small oligomers, which have mixed beta-sheet and random coil structures. The monomer is mostly a random coil with some residual compactness. Aggregated A beta(18-35) forms fibrils of width 3.0 +/- 0.7 nm, which is consistent with a hairpin shape. Each of these properties has a close similarity to A beta(40). Remarkably, solid state NMR indicates that the fibrils also retain the secondary structure and tertiary contacts of A beta(40). This is the shortest fragment of A beta reported so far which preserves its fibrillar architecture, including the hairpin turn, as well as its solution phase conformational properties. Residues 18-35 should therefore be a key target of AD therapeutics. (C) 2013 Published by Elsevier B. V.
Keywords: Alzheimer's disease; Fluorescence correlation spectroscopy; Protein aggregation; Solid-state NMR

Competition between adsorption and intrinsic collapse of full-length a beta 1-42 on the surface of a single-walled carbon nanotube: insights from molecular dynamics simulations - Sengupta, Neelanjana (Biophysical Journal, 2013)

Critical roles of key domains in complete adsorption of a beta peptide on single-walled carbon nanotubes: insights with point mutations and MD simulations - Jana, Asis K.; Jose, Jaya C.; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2013)
Owing to the influence of nanomaterials on biomacromolecular behavior, their potential applications are rapidly gaining attention. Based on atomistic molecular dynamics simulation studies we have recently reported that the full-length A beta peptide, whose self-assembly is associated with Alzheimer's disease, adsorbs rapidly on single-walled carbon nanotubes, thereby losing its natural propensity to collapse. Here, we investigate the mechanistic overlap between the peptide's compactification and its adsorption, while decoupling the roles of hydrophobicity and aromaticity via point mutations. The collapse mechanism is correlated with interactions between the central hydrophobic core (HP1) and the peptide's C-terminal domain, which are almost exactly compensated by interactions arising from the nanotube after complete adsorption. Adsorption is initiated by HP1 and consolidated by strong interactions arising from the N-terminal domain. Altering the hydrophobicity, but not the aromatic character, of the central residue in HP1 decreases the collapse probability. On the other hand, the adsorption propensity is dramatically reduced when either the hydrophobicity or the aromatic character in HP1 is compromised. The hydrophobicity of HP1 is responsible for dewetting transitions that facilitate its initial interactions with the nanotube, which then lead to very favorable interactions with the nanotube.

Molecular dynamics simulation studies of the structural response of an isolated A beta(1-42) monomer localized in the vicinity of the hydrophilic TiO2 surface - Jose, Jaya C.; Sengupta, Neelanjana (European Biophysics Journal, 2013)
We have probed the effect of a model hydrophilic surface, rutile TiO2, on the full-length amyloid beta (A beta(1-42)) monomer using molecular dynamics simulations. The rutile surface brings about sharp changes in the peptide's intrinsic behavior in a distance-dependent manner. The intrinsic collapse of the peptide is disrupted, while the beta-sheet propensity is sharply enhanced with increased proximity to the surface. The results may have implications for A beta self-assembly and fibrillogenesis on hydrophilic surfaces and should be taken into consideration in the design of novel nanomaterials for perturbing amyloidogenic behavior.
Keywords: Amyloid beta; beta-Sheet propensity; molecular dynamics simulation; TiO2 rutile surface

Surface induced collapse of A beta(1-42) with the F19A replacement following adsorption on a single walled carbon nanotube - Jana, Asis K.; Sengupta, Neelanjana (Biophysical Chemistry, 2013)
Spontaneous adsorption of the A beta peptide on the surface of a single-walled carbon nanotube, resulting in the prevention of its intrinsic propensity to form collapsed states, could be a plausible means to hinder the peptide's initial nucleation and self-assembly. We report here the effects of sharply reducing both aromatic and hydrophobic character within the peptide's central hydrophobic core on its free and surface behavior. In such an altered peptide, complete surface adsorption is found to induce, rather than prevent, the adsorbed peptide's collapse. The weakened surface interactions of the central hydrophobic core allow its greater translational mobility on the surface, thereby facilitating interactions that lead to compaction. Both the adsorption and the subsequent collapse are accompanied by a loss of surface hydration in the modified peptide. We further find that such a two-step dewetting leads to hydration levels comparable to that obtained after compaction of the free peptide. These insights may be leveraged for designing molecular surfaces for disrupting intrinsic A beta behavior. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Amyloid beta peptide; carbon nanotube; Lateral mobility; molecular dynamics simulation; Surface induced collapse

Atomistic simulations lend mechanistic insights into plausible ways of perturbing the nucleation thermodynamics of the full-length a beta peptide - Jana, Asis K.; Sengupta, Neelanjana (Biophysical Journal, 2014)

Cross dimerization of amyloid-beta and alpha synuclein proteins in aqueous environment: a molecular dynamics simulations study - Jose, Jaya C.; Chatterjee, Prathit; Sengupta, Neelanjana (Plos One, 2014)
Self-assembly of the intrinsically unstructured proteins, amyloid beta (A beta) and alpha synclein (alpha Syn), are associated with Alzheimer's Disease, and Parkinson's and Lewy Body Diseases, respectively. Importantly, pathological overlaps between these neurodegenerative diseases, and the possibilities of interactions between A beta and alpha Syn in biological milieu emerge from several recent clinical reports and in vitro studies. Nevertheless, there are very few molecular level studies that have probed the nature of spontaneous interactions between these two sequentially dissimilar proteins and key characteristics of the resulting cross complexes. In this study, we have used atomistic molecular dynamics simulations to probe the possibility of cross dimerization between alpha Syn(1-95) and A beta(1-42), and thereby gain insights into their plausible early assembly pathways in aqueous environment. Our analyses indicate a strong probability of association between the two sequences, with inter-protein attractive electrostatic interactions playing dominant roles. Principal component analysis revealed significant heterogeneity in the strength and nature of the associations in the key interaction modes. In most, the interactions of repeating Lys residues, mainly in the imperfect repeats `KTKEGV' present in alpha Syn(1-95) were found to be essential for cross interactions and formation of inter-protein salt bridges. Additionally, a hydrophobicity driven interaction mode devoid of salt bridges, where the non-amyloid component (NAC) region of alpha Syn(1-95) came in contact with the hydrophobic core of A beta(1-42) was observed. The existence of such hetero complexes, and therefore hetero assembly pathways may lead to polymorphic aggregates with variations in pathological attributes. Our results provide a perspective on development of therapeutic strategies for preventing pathogenic interactions between these proteins.

Microscopic hydration properties of the a beta(1-42) peptide monomer and the globular protein ubiquitin: a comparative molecular dynamics study - Jose, Jaya C.; Khatua, Prabir; Bansal, Nupur; Sengupta, Neelanjana; Bandyopadhyay, Sanjoy (Journal of Physical Chemistry B, 2014)
Atomistic molecular dynamics simulations of eight selected conformations of a disordered protein amyloid beta (1-42) (A beta), and a globular protein, ubiquitin(UBQ), have been carried out in aqueous media at 310 K. Detailed analyses were carried out to compare the microscopic properties of water molecules present in the hydration layers of these systems. It is notices that irrespective of the conformational heterogeneity among the A beta monomers, water molecules hydrating UBQ. Importantly, the conformational heterogeneity of the A beta monomers has been found to affect the translational and rotational motions of hydration water molecules in a nonuniform manner. Detailed investigation of the timescale of hydrogen bond relaxations at the surface and their energetics revealed the possibility of heterogeneous confinement around different A beta conformations. The distribution of water density fluctuation around A beta conformations are broader compared density fluctuation among the A beta monomers suggests that the structural propensities could affect the peptides effective surface hydrophobicity.

Molecular investigations of protriptyline as a multi-target directed ligand in alzheimer's disease - Bansode, Sneha B.; Jana, Asis K.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Joshi, Rakesh S.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (Plos One, 2014)
Alzheimer's disease (AD) is a complex neurodegenerative disorder involving multiple cellular and molecular processes. The discovery of drug molecules capable of targeting multiple factors involved in AD pathogenesis would greatly facilitate in improving therapeutic strategies. The repositioning of existing non-toxic drugs could dramatically reduce the time and costs involved in developmental and clinical trial stages. In this study, preliminary screening of 140 FDA approved nervous system drugs by docking suggested the viability of the tricyclic group of antidepressants against three major AD targets, viz. Acetylcholinesterase (AChE), beta-secretase (BACE-1), and amyloid beta (A beta) aggregation, with one member, protriptyline, showing highest inhibitory activity. Detailed biophysical assays, together with isothermal calorimetry, fluorescence quenching experiments, kinetic studies and atomic force microscopy established the strong inhibitory activity of protriptyline against all three major targets. The molecular basis of inhibition was supported with comprehensive molecular dynamics simulations. Further, the drug inhibited glycation induced amyloid aggregation, another important causal factor in AD progression. This study has led to the discovery of protriptyline as a potent multi target directed ligand and established its viability as a promising candidate for AD treatment.

Non-uniform early structural response of globular proteins to cold denaturing conditions: a case study with Yfh1 - Chatterjee, Prathit; Bagchi, Sayan; Sengupta, Neelanjana (Journal of Chemical Physics, 2014)
The mechanism of cold denaturation in proteins is often incompletely understood due to limitations in accessing the denatured states at extremely low temperatures. Using atomistic molecular dynamics simulations, we have compared early (nanosecond timescale) structural and solvation properties of yeast frataxin (Yfh1) at its temperature of maximum stability, 292 K (T-s), and the experimentally observed temperature of complete unfolding, 268 K (T-c). Within the simulated timescales, discernible ``global'' level structural loss at T-c is correlated with a distinct increase in surface hydration. However, the hydration and the unfolding events do not occur uniformly over the entire protein surface, but are sensitive to local structural propensity and hydrophobicity. Calculated infrared absorption spectra in the amide-I region of the whole protein show a distinct red shift at T-c in comparison to T-s. Domain specific calculations of IR spectra indicate that the red shift primarily arises from the beta strands. This is commensurate with a marked increase in solvent accessible surface area per residue for the beta-sheets at T-c. Detailed analyses of structure and dynamics of hydration water around the hydrophobic residues of the beta-sheets show a more bulk water like behavior at T-c due to preferential disruption of the hydrophobic effects around these domains. Our results indicate that in this protein, the surface exposed beta-sheet domains are more susceptible to cold denaturing conditions, in qualitative agreement with solution NMR experimental results. (C) 2014 AIP Publishing LLC.

Beta self-association and adsorption on a hydrophobic nanosurface: competitive effects and the detection of small oligomers via electrical response - Jana, Asis K.; Sengupta, Neelanjana (Soft Matter, 2015)
Treatment of Alzheimer's disease (AD) is impeded by the lack of effective early diagnostic methods. Small, soluble A beta globulomers play a major role in AD neurotoxicity, and detecting their presence in aqueous fluids could lead to suitable sensors. We evaluate the adsorption behavior of small A beta oligomers on the surface of a single walled carbon nanotube of high curvature. While the intrinsic self-assembly propensity of A beta is markedly hindered by adsorption, the oligomeric units show high degrees of surface immobilization. Immobilized complexes are capable of oligomeric growth, but with a shifted monomer-oligomer equilibrium compared to the free states. In the presence of an ionic solution and suitable external electric fields, magnitudes of the current blockades are found to be sensitive to the oligomeric number of the adsorbed complex. However, this sensitivity gradually diminishes with increasing oligomeric size. The results provide a proof-of-concept basis for further investigations in the design of sensors for detecting the toxic small oligomers of A beta.

Perturbations in inter-domain associations may trigger the onset of pathogenic transformations in PrPC: insights from atomistic simulations - Menon, Sneha; Sengupta, Neelanjana (Molecular Biosystems, 2015)
Conversion of the predominantly alpha-helical cellular prion protein (PrPC) to the misfolded beta-sheet enriched Scrapie form (PrPSc) is a critical event in prion pathogenesis. However, the conformational triggers that lead to the isoform conversion (PrPC to PrPSc) remain obscure, and conjectures about the role of unusually hydrophilic, short helix H1 of the C-terminal globular domain in the transition are varied. Helix H1 is anchored to helix H3 via a few stabilizing polar interactions. We have employed fully atomistic molecular dynamics simulations to study the effects triggered by a minor perturbation in the network of these non-bonded interactions in PrPC. The elimination of just one of the key H1-H3 hydrogen bonds led to a cascade of conformational changes that are consistent with those observed in partially unfolded intermediates of PrPC, with pathogenic mutations and in low pH environments. Our analyses reveal that the perturbation results in the enhanced conformational flexibility of the protein. The resultant enhancement in the dynamics leads to overall increased solvent exposure of the hydrophobic core residues and concomitant disruption of the H1-H3 inter-domain salt bridge network. This study lends credence to the hypothesis that perturbing the cooperativity of the stabilizing interactions in the PrPC globular domain can critically affect its dynamics and may lead to structural transitions of pathological relevance.

Tolbutamide induces conformational change and promotes albumin glycation - Bansode, Sneha B.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Jana, Asis K.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (RSC Advances, 2015)
Tolbutamide is a first generation sulfonylurea drug used for the treatment of type II diabetes. In the present study, the effect of tolbutamide on albumin conformation was investigated using BSA as a model protein. The binding of tolbutamide induced a conformational change in albumin, which was confirmed by thioflavin T assay, ANS assay, and CD spectroscopy. Computer simulations suggested that the binding of tolbutamide increases the solvent accessibility of lysine residues, the hotspots of glycation. Furthermore, the change in conformation of albumin facilitates increased glycation, which was observed by AGE specific fluorescence and the results were corroborated by mass spectrometric analysis. This study suggested that tolbutamide enhances albumin glycation by inducing conformational change in BSA and hence could be a potential risk factor if used for a prolonged period.

Conformational energy landscape of the ritonavir molecule - Chakraborty, Debayan; Sengupta, Neelanjana; Wales, David J. (Journal of Physical Chemistry B, 2016)
Conformational polymorphism of ritonavir, a well-known pharmaceutical drug, is intricately linked to its efficacy in the treatment of acquired immunodeficiency syndrome (AIDS). Polymorphic transition from the crystalline form I to form II leads to the loss of bioactivity. The constituent ritonavir molecules adopt a trans configuration about the carbamate torsion angle in the form I crystal, and a cis configuration in the form II crystal. Investigating the energetics and mechanistic features of conformational transitions at the single molecule level is a key step toward decoding the complex features of the solid state polymorphism. In this work, we employ the energy landscape framework to investigate the conformational transitions of an isolated ritonavir molecule. The landscape is explored using discrete path sampling (DPS) and visualized in terms of disconnectivity graphs. We identify two distinct funnels corresponding to the two molecular forms that are identified by crystallography. The two regions can be reliably distinguished using the carbamate torsion angle, and the corresponding interconversion rates are predicted to follow Arrhenius behavior. The results provide mechanistic insight into pathways for cis <-> trans interconversion at the molecular level and may also help in elucidating the polymorphic transitions in the crystal state.

Conformational features of the Aβ42 peptide monomer and its interaction with the surrounding solvent - Khatua, Prabir; Jose, Jaya C.; Sengupta, Neelanjana; Bandyopadhyay, Sanjoy (Physical Chemistry Chemical Physics, 2016)

Glycation induces conformational changes in Amyloid-? peptide and enhances its aggregation propensity: molecular insights - Jana, Asis K.; Batkulwar, Kedar B.; Kulkarni, Mahesh J.; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2016)

Hydralazine inhibits amyloid beta (Aβ) aggregation and glycation and ameliorates Aβ1–42 induced neurotoxicity - Batkulwar, Kedar B.; Jana, Asis K.; Godbole, Rashmi K.; Khandelwal, Puneet; Sengupta, Neelanjana; Kulkarni, Mahesh J. (RSC Advances, 2016)

Signatures of protein thermal denaturation and local hydrophobicity in domain specific hydration behavior: a comparative molecular dynamics study - Chatterjee, Prathit; Sengupta, Neelanjana (Molecular Biosystems, 2016)
We investigate, using atomistic molecular dynamics simulations, the association of surface hydration accompanying local unfolding in the mesophilic protein Yfh1 under a series of thermal conditions spanning its cold and heat denaturation temperatures. The results are benchmarked against the thermally stable protein, Ubq, and behavior at the maximum stability temperature. Local unfolding in Yfh1, predominantly in the beta sheet regions, is in qualitative agreement with recent solution NMR studies; the corresponding Ubq unfolding is not observed. Interestingly, all domains, except for the beta sheet domains of Yfh1, show increased effective surface hydrophobicity with increase in temperature, as reflected by the density fluctuations of the hydration layer. Velocity autocorrelation functions (VACF) of oxygen atoms of water within the hydration layers and the corresponding vibrational density of states (VDOS) are used to characterize alteration in dynamical behavior accompanying the temperature dependent local unfolding. Enhanced caging effects accompanying transverse oscillations of the water molecules are found to occur with the increase in temperature preferentially for the beta sheet domains of Yfh1. Helical domains of both proteins exhibit similar trends in VDOS with changes in temperature. This work demonstrates the existence of key signatures of the local onset of protein thermal denaturation in solvent dynamical behavior.

Unraveling origins of the heterogeneous curvature dependence of polypeptide interactions with carbon nanostructures - Jana, Asis K.; Tiwari, Mrityunjay K.; Vanka, Kumar; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2016)
Emerging nanotechnology has rapidly broadened interfacial prospects of biological molecules with carbon nanomaterials (CNs). A prerequisite for effectively harnessing such hybrid materials is a multifaceted understanding of their complex interfacial interactions as functions of the physico-chemical characteristics and the surface topography of the individual components. In this article, we address the origins of the curvature dependence of polypeptide adsorption on CN surfaces (CNSs), a phenomenon bearing an acute influence upon the behavior and activity of CN-protein conjugates. Our benchmark molecular dynamics (MD) simulations with the amphiphilic full-length amyloid beta (A beta) peptide demonstrate that protein adsorption is strongest on the concave (inner) CN-surface, weakest on the convex (outer) surface, and intermediary on the planar surface, in agreement with recent experimental reports. The curvature effects, however, are found to manifest non-uniformly between the amino acid subtypes. To understand the underlying interplay of the chemical nature of the amino acids and surface topography of the CNs, we performed high-level quantum chemical (QM) calculations with amino acid analogs (MA) representing their five prominent classes, and convex, concave and planar CN fragments. Molecular electrostatic potential maps reveal pronounced curvature dependence in the mixing of electron densities, and a resulting variance in the stabilization of the non-covalentty bound molecular complexes. Interestingly, our study revealed that the interaction trends of the high-level QM calculations were captured well by the empirical force field. The findings in this study have important bearing upon the design of carbon based bio-nanomaterials, and additionally, provide valuable insights into the accuracy of various computational techniques for probing non-bonded interfacial interactions.

Influence of hyperglycemic conditions on self-association of the alzheimer's amyloid beta (a beta(1-42)) peptide - Menon, Sneha; Sengupta, Neelanjana (ACS Omega, 2017)
<div id="absImg" style="position: relative; margin: 0px; padding: 5px; border: 1px solid rgb(204, 204, 204); border-radius: 5px; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; text-align: center; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;"><img alt="Abstract Image" src="http://pubs.acs.org/appl/literatum/publisher/achs/journals/content/acsodf/2017/acsodf.2017.2.issue-5/acsomega.7b00018/20170517/images/medium/ao-2017-00018p_0003.gif" style="border: 0px; max-width: 100%;"> <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Clinical studies have identified a correlation between type-2 diabetes mellitus and cognitive decrements en route to the onset of Alzheimer’s disease (AD). Recent studies have established that post-translational modifications of the amyloid β (Aβ) peptide occur under hyperglycemic conditions; particularly, the process of glycation exacerbates its neurotoxicity and accelerates AD progression. In view of the assertion that macromolecular crowding has an altering effect on protein self-assembly, it is crucial to characterize the effects of hyperglycemic conditions via crowding on Aβ self-assembly. Toward this purpose, fully atomistic molecular dynamics simulations were performed to study the effects of glucose crowding on Aβ dimerization, which is the smallest known neurotoxic species. The dimers formed in the glucose-crowded environment were found to have weaker associations as compared to that of those formed in water. Binding free energy calculations show that the reduced binding strength of the dimers can be mainly attributed to the overall weakening of the dispersion interactions correlated with substantial loss of interpeptide contacts in the hydrophobic patches of the Aβ units. Analysis to discern the differential solvation pattern in the glucose-crowded and pure water systems revealed that glucose molecules cluster around the protein, at a distance of 5–7 Å, which traps the water molecules in close association with the protein surface. This preferential exclusion of glucose molecules and resulting hydration of the Aβ peptides has a screening effect on the hydrophobic interactions, which in turn diminishes the binding strength of the resulting dimers. Our results imply that physical effects attributed to crowded hyperglycemic environments are incapable of solely promoting Aβ self-assembly, indicating that further mechanistic studies are required to provide insights into the self-assembly of post-translationally modified Aβ peptides, known to possess aggravated toxicity, under these conditions.
Keywords: Conformation; Drug discovery and Drug delivery systems; Free energy; Glycoproteins; Molecular association; Molecular dynamics simulation

Structural and dynamics studies of the TetR family protein, CprB from Streptomyces coelicolor in complex with its biological operator sequence - Bhukya, Hussain; Jana, Asis K.; Sengupta, Neelanjana; Anand, Ruchi (Journal of Structural Biology, 2017)
In Streptomycetes, tetracycline repressor family of transcription regulators (TetR-FTRs) controls various biological processes including antibiotic biosynthesis, cellular morphology and innate resistance. Here, we focus on understanding the structural basis of transcription regulation by CprB, a member of TetR-FTRs from S. coelicolor. CprB is implicated as a receptor of gamma-butyrolactones, a class of quorum sensing molecules, responsible for initiating secondary metabolic pathways. In order to understand the molecular mechanism of DNA recognition, the X-ray structure of CprB in complex with its biological relevant operator sequence was solved to a resolution of 3.95 angstrom. Furthermore, to refine and compliment the results, atomistic molecular dynamics simulations were carried out using the X-ray structure as the template. The studies reveal that CprB binds to DNA as dimer of dimers with this mode of interaction results in minimal distortion in the DNA, enabling these proteins to recognize multiple sequences with varying affinity. Another crucial finding from our simulation results was that the positively charged N-terminal arm of CprB brings extra stability to the protein-DNA complex by interacting with the minor-groove of the DNA and anchoring itself to the phosphate backbone. Corroborating electrophoretic mobility shift assay and fluorescence anisotropy experiments showed that the mutant AN6-CprB exhibited about 7-8 fold reduced DNA binding. Comparison with other TetR-FTRs reveals that this strategy is also employed by over 25% of TetR-FTRs, where N-terminal anchoring mechanism is used to enhance selectivity for a particular DNA sequence. (C) 2017 Elsevier Inc. All rights reserved.

Effect of hyperglycemic conditions on the early self-assembly of the alzheimer's amyloid beta peptide: implications for neurotoxicity - Menon, Sneha; Sengupta, Neelanjana (Biophysical Journal, 2018)

Cold thermal response of an amyloid oligomer differs from typical globular protein cold denaturation - Menon, Sneha; Sengupta, Neelanjana (Journal of Physical Chemistry Letters, 2019)
In contrast with the general behavior of folded proteins, the cold thermal response of amyloid assemblies is difficult to elicit with simple models. We exploit exhaustive simulations to evaluate the thermal response of a barrel-shaped model amyloid oligomer, with a distinct hydrophobic core akin to that of folded proteins. Cumulative thermal data over the range of 210-483 K indicate a sharp inflection and rise in structural stability as the temperature is decreased below the melting temperature of the water model. This is not commensurate with the equilibrium free energy profile obtained with core packing as the order parameter. However, energetic analyses and the size of their fluctuations indicate the crucial role of hydration in mediating structural transitions, beyond the expected temperature-dependent hydrophobic effect. Structural ordering of the hydration layer over bulk water is maximized at the transition and vanishes at high temperatures. This is a first direct demonstration of the microscopic influence of hydration water on the low-temperature response of an amyloid assembly close to the cryo-regime.

Influence of crowding and surfaces on protein amyloidogenesis: A thermo-kinetic perspective - Menon, Sneha; Sengupta, Neelanjana (Biochimica ET Biophysica Acta-Proteins and Proteomics, 2019)
The last few decades have irreversibly implicated protein self-assembly and aggregation leading to amyloid fibril formation in proteopathies that include several neurodegenerative diseases. Emerging studies recognize the importance of eliciting the pathways leading to protein aggregation in the context of the crowded intracellular environment rather than in conventional in vitro conditions. It is found that crowded environments can have acceleratory as well as inhibitory effects on protein aggregation, depending on the interplay of underlying factors on the crucial rate limiting steps. The aggregation mechanism and transient species formed along the pathway are further altered when they interface with natural and artificial surfaces in the cellular milieu. An increasing number of studies probe the autocatalytic nature of amyloid surfaces as well as membrane bilayer effects on amyloidogenesis. Moreover, exposure to modern nanosurfaces via nanomedicines and other sources potentially invokes beneficial or deleterious biological response that needs rigorous investigation. Mounting evidences indicate that nanoparticles can either promote or impede amyloid aggregation, spurring efforts to tune their interactions for developing effective anti-amyloid strategies. Mechanistic insights into nanoparticle mediated aggregation pathways are therefore crucial for engineering anti-amyloid nanoparticle strategies that are biocompatible and sustainable. This review is a compilation of studies that contribute to the current understanding of the altering effects of molecular crowding as well as natural and artificial surfaces on protein amyloidogenesis.

Nanoscale interplay of membrane composition and amyloid self-assembly - Menon, Sneha; Sengupta, Neelanjana; Das, Payel (Journal of Physical Chemistry B, 2020)
Cell membranes are complex assemblies of lipids and proteins exhibiting lipid compositional heterogeneity between the inner and outer leaflets of the bilayer. Aberrant protein aggregation, implicated in a number of neurodegenerative diseases including Alzheimer's, is known to result in both extracellular and intracellular deposits with divergent pathophysiological effects. Mounting evidence substantiates membrane-mediated amyloid effects and indicates membrane composition, particularly gangliosides, as a plausible factor influencing the fibrillation process. By employing exhaustive molecular dynamics simulations using a coarse-grained model, we probed the assembly behavior of amyloidogenic A beta(12-28) peptides on the chemically heterogeneous extracellular (outer) and cytosolic (inner) leaflets of a mammalian plasma membrane. Our results indicate that the compositional nature of the membrane has a crucial impact on the peptide self-assembly. Peptide oligomerization is hindered on the outer leaflet relative to the inner leaflet due to a competition between interpeptide and peptide-membrane interactions, resulting in higher population of smaller oligomers. The weaker associations among peptides on the outer membrane can be attributed to the favorable interactions of the peptides with gangliosides (GM) that characterize the extracellular membrane. At a higher peptide:GM ratio, we observe enhanced nanoclustering of GM lipids mediated by preferential GM-A beta binding. Interaction between peptide and GM further impacts local membrane curvature; there is a concomitant loss in membrane concavity due to looser GM packing. Our simulations provide molecular insights into the role of membrane composition on A beta aggregation and lend credence to earlier reports of ganglioside-mediated A beta aggregation in the outer membrane. We also demonstrate the effects of local peptide assemblies on the membrane structure and dynamics.